Evaluation of the current performance of the rainwater in Lattakia and construction a drainage network model using sewer gems - محمد سليمان; هيثم شاهين; رائد جعفر (Latakia University Journal -Engineering Sciences Series, 2023)
Lattakia city has a high annual rainfall and since it has various terrain; its streets hasn’t got the same rate and they have big leanings, it has more byways than main streets and the amount of rainfall is the same in the entire city, rainwater is drained to the sewage network which causes floods in the streets and traffic accidents. In this research we have constructed a scheme for the current network and draw it on the GIS program and determine the pipes diameters and sewage outfalls, Then the state of the rainwater drainage and household water drainage. We considered the network capacity for the current exuberance, so the current network diameters and rates, as well as the sewerage and the rainfall drainage amount were implemented to Sewer Gems program to analyze the system ability to drain this exuberance, the analysis showed drainage malfunction in most of these main streets, independent rainwater network was designed with Sewer Gems program, It chose three main outfalls and designed the network based on them, in order to give results of the design (diameters-speed-drilling depth).